Implementation of statistical process control for quality control cycle in the various industry in Indonesia: A systematic literature review - Hibarkah Kurnia; Setiawan Setiawan; Mohammad Hamsal (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
A systematic literature review is a rigorous method of assessing and combining research results compared to the usual literature review, which consists of annotated bibliographies, a systematic review of the existing literature regarding specific research questions on a topic of interest. Statistical Process Control (SPC) is a well-established technique in a context that has recently been used in software production. Software production is not like manufacturing because it requires more human resources and machines, resulting in an item's one-time production. It is therefore essential to assess what SPC works in a software context. Thus, this consideration has motivated us to define and conduct an evaluation review to assess whether SPC is used effectively and genuinely Quality Control Cycle (QCC) in Indonesia's various industries. According to a systematic literature review process, an established protocol was revised and refined by the authors. This journal collection of journals has been used in various industries in Indonesia. We report our preliminary considerations and results in a systematic review on the SPC and find 30 journals collected as references for readers in making research journals related to SPC. Our products and first impressions are favorable. This journal collection can also make it easier for researchers to get the desired journal references.